On the stability of a trivial invariant torus of one class of impulsive systems - Dudzyanyi, S. I.; Perestyuk, N. A. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We consider the problem of asymptotic stability of the trivial invariant torus of one class of impulsive systems. Sufficient criteria of asymptotic stability are obtained by the method of freezing in one case, and by the direct Lyapunov method for the investigation of stability of solutions of impulsive systems in another case.